2017
DOI: 10.5688/ajpe6076
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Shared Values for School-Affiliated Student Organizations

Abstract: Objective. To identify shared values for student organizations. Methods. A three-round Delphi approach was utilized to identify and prioritize shared values among student organization leadership. In round 1, student leaders selected 15 values from a list of 36 organizational values and were given an opportunity to include up to five suggestions not incorporated within the original list. Student leaders narrowed the 15 values to 12 in round 2. The top 12 priorities were ranked in round 3 and participants were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…With the aim of improving programs and of developing the pharmacist profession in accordance with the international recommendations in line with the evolution of patients’ health-related needs, Bush et al [ 18 ] address student organizations in their paper. The authors present the importance of knowing the values of such organizations in order to adapt programs and curricula, and involve students in the evolution of their profession.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of improving programs and of developing the pharmacist profession in accordance with the international recommendations in line with the evolution of patients’ health-related needs, Bush et al [ 18 ] address student organizations in their paper. The authors present the importance of knowing the values of such organizations in order to adapt programs and curricula, and involve students in the evolution of their profession.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] 2011 Commentary Nepal Global disparities in public health Bush AA, et al Identifying Shared Values for School-Affiliated Student Organizations. [ 18 ] 2017 Empirical study USA Adapting training to change King AE, et al A Required Online Course with a Public Health Focus for Third Professional Year Pharmacy Students. [ 16 ] 2015 Empirical study USA Adapting training to change Offiong CY, et al The role of colleges and schools of pharmacy in the advent of Healthy People 2020.…”
mentioning
confidence: 99%
“…Two other definitions were commonly cited: the leader as an agent of change (nine articles) and the leader as an individual who receives external recognition for leadership, eg, serving in a formal position, receiving an award (nine articles). Some articles defined leadership in terms of the position held (eg, president), 19,20 whereas others indicated that any position was sufficient, including involvement on a committee or task force. Demonstrating leadership without a formal title or position was the fourth most common definition (six articles); "big l" versus "little l" leadership was a common framework used to distinguish between individuals with formal leadership roles and those who lead informally.…”
Section: Resultsmentioning
confidence: 99%
“…The surveys were classified for hospital pharmacists and community pharmacists and distributed electronically using Qualtrics XM (Qualtrics, Provo, UT, USA). This method was adapted from a similar study by Bush et al (2017) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%